2023
DOI: 10.1007/s00701-023-05509-6
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic measurements for the prediction of dysphagia after occipitocervical fusion: a systematic review

Abstract: Background Occipitocervical fusion (OCF) is a procedure performed for multiple upper cervical pathologies. A common postprocedural complication of OCF is dysphagia, which has been linked to the narrowing of the pharyngeal space due to fixation in a hyper-flexed angle. Postoperative dysphagia is linked to reduced quality of life, prolonged hospital stay, aspiration pneumonia, and increased mortality. This has led to investigations of the association between sagittal radiographic angles and dysphag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
(111 reference statements)
1
8
0
Order By: Relevance
“…Previous studies have reported 10–25% dysphagia after OCF at long-term follow-up, and our results are in line with these reports [ 28 ]. In this study, 53% of the individuals reported any dysphagia and 27% moderate to severe dysphagia.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have reported 10–25% dysphagia after OCF at long-term follow-up, and our results are in line with these reports [ 28 ]. In this study, 53% of the individuals reported any dysphagia and 27% moderate to severe dysphagia.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, it was shown that approximately 25% of patients undergoing OCF experienced dysphagia at short-term follow-up. However, at long-term follow-up (12–72 months), resolution of the swallowing difficulties was seen in one-third of these patients [ 28 ]. Efforts to predict and prevent postoperative dysphagia are crucial as this complication has been associated with prolonged hospital stay, reduced health-related quality of life (HRQoL) [ 25 ], and increased mortality [ 3 , 11 , 12 , 20 , 27 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Postoperative dysphagia after OC fusion occurred in 26% of patients, perhaps caused by hyperflexion or misalignment of the upper cervical spine during OC fusion, resulting in pharyngeal stenosis. 28,29 The LC1-PC2 fixation, which provides high biomechanical strength, has become the most popular treatment for AAI. 2,3 Compared with OC fusion, LC1-PC2 fixation does not limit the movement of the occiput-C1 complex, significantly improving postoperative satisfaction and neck mobility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a longer wound incision, implant failure and postoperative dysphagia are other concerns with OC fusion 27 . Postoperative dysphagia after OC fusion occurred in 26% of patients, perhaps caused by hyperflexion or misalignment of the upper cervical spine during OC fusion, resulting in pharyngeal stenosis 28,29 …”
Section: Discussionmentioning
confidence: 99%